2020
DOI: 10.1039/c9ra09147e
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Ti3O5 hierarchical porous microspheres with an enhanced photothermal property

Abstract: Metallic γ-Ti3O5 hierarchical porous microspheres with strong localized surface plasmon resonance are reported, which can inhibit cancer cell viability in vitro and disrupt tumor tissue growth in vivo under the irradiation of near infrared light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Examples of this type of structures are non-stoichiometric materials with oxygen/metal vacancies, mixed metal valences and/or conduction electrons. 30,[293][294][295] An appealing precedent of this approach was recently reported by Ozin and co-workers in the photo-thermal hydrogenation of CO 2 using the non-stoichiometric black In 2 O 3Àx /In 2 O 3 catalyst. 46 The authors found that the hydrogenation of pale yellow In 2 O 3 at different temperatures led to the generation of black nonstoichiometric heterostructures composed of In 2 O 3Àx domains in crystalline stoichiometric In 2 O 3 .…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…Examples of this type of structures are non-stoichiometric materials with oxygen/metal vacancies, mixed metal valences and/or conduction electrons. 30,[293][294][295] An appealing precedent of this approach was recently reported by Ozin and co-workers in the photo-thermal hydrogenation of CO 2 using the non-stoichiometric black In 2 O 3Àx /In 2 O 3 catalyst. 46 The authors found that the hydrogenation of pale yellow In 2 O 3 at different temperatures led to the generation of black nonstoichiometric heterostructures composed of In 2 O 3Àx domains in crystalline stoichiometric In 2 O 3 .…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…Both Ti 2 O 3 and Ti 3 O 5 have been reported for their high-performance photothermal conversion [ 9 , 31 ]. The increase in surface temperature shows a significant positive correlation with the content of Ti 2 O 3 and Ti 3 O 5 phases in black films.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] The same light to heat conversion mechanism holds in different nanomaterials featuring LSPRs. This is the case of semiconductor nanocrystals with appreciable free carriers concentration, like Cu chalcogenides,[ 82 , 83 , 84 , 85 ] zinc oxide, [86] ITO (indium tin oxide), [87] nonstoichiometric titanium oxides [88] or molybdenum [89] oxides. In these NP the LSPR band maximum can be tuned (usually in the NIR region) by tuning the doping degree and/or the stoichiometry.…”
Section: Pte: Basic Concepts and Mechanismsmentioning
confidence: 99%